Energy Colonialism Powers the Ongoing Unnatural Disaster in Puerto Rico - de Onís, Catalina M. (Frontiers in Communication, 2018)
On September 20, 2017, Hurricane María made landfall in Puerto Rico. Blasting the Caribbean archipelago with 155-mile-per-hour winds, this, in many ways, unnatural disaster exposed the brutal consequences of energy colonialism and an extractivist economy, as well as ongoing and increasing advocacy for decentralized solar infrastructure by many local residents and other renewables supporters. This paper argues that acknowledging colonial power relations is essential for studying the significance of energy democracy in Puerto Rico and the interplay of energy systems, environments, and stakeholders. To support this claim, this essay outlines Puerto Rico’s history as a US colony by focusing on key policies and their implications; examines openings for and barriers to decentralized, community solar in Puerto Rico; and concludes by discussing future research directions on just energy transitions and the imperative of uprooting colonialism and agitating for community self-determination and energy justice in these transformations.